Elektromedis dalam Pengelolaan Peralatan Elektromedik untuk Pelayanan Kesehatan - Agung Kridoyono; Elvianto Dwi Hartono; Bagus Hardiansyah; Anton Breva Yunanda; Mochamad Shidqon; Istantyo Yuwono (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This article about community service activities discusses the transformation of the electromedical profession as a response to technological developments in the management of electromedical equipment with the aim of improving the quality of health services. This transformation includes changes in the roles, skills and responsibilities of electromedical professionals to adapt and optimize increasingly complex electromedical equipment. The results of this workshop show that the transformation of the electromedical profession has a positive impact on the management of electromedical equipment and the quality of health services. Electromedical professionals involved in this transformation experience increased competency and effectiveness in caring for, maintaining, and repairing electromedical equipment. Apart from that, the application of the latest technology also allows for more efficient monitoring and management of electromedical equipment. Keywords: Transformation of the electromedical profession, electromedical maintenance, electromedical monitoring